2014
DOI: 10.1080/15567249.2010.514586
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Analysis of CO2Emissions and the GDP Relationship: Empirical Evidence from High-income OECD Countries

Abstract: A positive relationship between carbon dioxide (CO 2 ) emissions and gross domestic product (GDP) is shown in this article; examining the per capita income and CO 2 emissions of 20 high-income countries for . It also appears that there is a positive relation from GDP to CO 2 except for Norway. While we found the coefficients for individual countries to be from 0.27-1.73, the panel varies from 0.70-1.03 in terms of time dummies effect. On the other hand, when we examine dynamic ordinary least squares (DOLS) est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…34,35 Table 1 presents a brief summary of the EKC hypothesis literature. As seen in Table 1, some researchers 12,3649 reached a bell-shaped relationship among income increase and pollution while some of them 5060 got mixed results and some others 9,61,62 could not find any evidence of the EKC hypothesis.…”
Section: Introductionmentioning
confidence: 96%
“…34,35 Table 1 presents a brief summary of the EKC hypothesis literature. As seen in Table 1, some researchers 12,3649 reached a bell-shaped relationship among income increase and pollution while some of them 5060 got mixed results and some others 9,61,62 could not find any evidence of the EKC hypothesis.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, taking into account the importance of the transport sector to the European economy, it is crucial to incentivize radical changes to achieve substantial improvements in transportation environmental performance. Ucak, Aslan, Yucel and Turgut (2015) found a positive association between economic growth and CO 2 emissions, which varied significantly across low-income and high-income countries. Similar evidence was produced by Begum, Sohag, Abdullah and Jaafar (2015).…”
Section: Transportation and Its Environmental Effectsmentioning
confidence: 90%
“…Following existing literature, which has explored the dynamic relationship between the environment and economic growth, diverse outcomes have been observed, largely depending on the selected sample, period, explanatory variables, and estimation technique (for example Basar and Tosun, 2021;Dogan and Inglesi-Lotz, 2020;Georgiev and Mihaylov, 2015; among others). The majority of empirical studies have indicated that economic growth is associated with an increase in pollution levels (Ben Jebli et al, 2016;Uçak et al, 2015;Saidi and Hammami, 2016), while few others have shown that the growth of value-added leads to a reduction in emission rates in the long term (Ben Jebli and Ben Youssef, 2015;AlKars et al, 2022;Nguyen, et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%